Evaluation of banana cultivars and hybrids in four production cycles - e Silva, Sebastião de Oliveira; Flores, José Cláudio de Oliveira; Neto, Francisco Pinheiro Lima (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> New productive banana hybrids, presenting good fruits and disease resistant, have been generated at Embrapa-Centro Nacional de Pesquisa de Mandioca e Fruticultura Tropical. The objective of this work was to evaluate some of these genotypes in four production cycles, to recommend them to the farmers. The experiment was carried out in the completely randomized design with 18 replications in Cruz das Almas, BA, Brazil. The genotypes evaluated were the varieties Grande-Naine, Nanica, Nam, Thap Maeo, Mysore, Caipira, Prata-Comum, Pacovan and Prata-Anã and the hybrids Pioneira, PA03-22, FHIA-18, PV03-76, PV03-44 and JV03-15. The characteristics analyzed were plant height, pseudostem diameter, bunch weight, number of fruits, fruit length and cycle. Along the cycles, 'Nanica' presented the smallest plant height, while 'Prata-Anã' stood out in the pseudostem diameter, followed by 'Prata-Comum' and JV03-15. 'Thap Maeo' stood out in the bunch weight and in the number of fruits, followed by FHIA-18, in the first character, and by 'Mysore', 'Caipira' and FHIA-18, in the second. 'Grande-Naine' and 'Nanica' presented the largest fruit length, while FHIA-18 and PA03-22 stood out in the precocity. It was concluded that 'Thap Maeo' has potential to substitute 'Mysore', and the hybrids evaluated present quality to be recommended to the farmers.